2016
DOI: 10.1016/j.paid.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Nine beautiful things: A self-administered online positive psychology intervention on the beauty in nature, arts, and behaviors increases happiness and ameliorates depressive symptoms

Abstract: We tested the effectiveness of a self-administered online positive psychology intervention which addressed the appreciation of beauty and excellence on happiness and depression directly after the intervention, after one week, and one, three, and six months. One hundred thirteen adults were randomly assigned to a "9 beautiful things" intervention (IG; n = 59), or a placebo control group ("early memories"; n = 54). Participants in the IG were asked to write down (a) three beautiful things in human behavior; (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
0
24
0
2
Order By: Relevance
“…Participants in the compassion condition experienced greater increases on the Steen Happiness Index compared to the control over the 6-month follow-up period. Similarly, Proyer et al (2016) randomized 113 adults to write about nine beautiful things (three in human behavior, three in nature or the environment, and three beauty in general) every evening for a week or to a control condition in which they wrote about early memories. Assessments showed significant increases on the Authentic Happiness Inventory in the intervention condition at all follow-up points.…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the compassion condition experienced greater increases on the Steen Happiness Index compared to the control over the 6-month follow-up period. Similarly, Proyer et al (2016) randomized 113 adults to write about nine beautiful things (three in human behavior, three in nature or the environment, and three beauty in general) every evening for a week or to a control condition in which they wrote about early memories. Assessments showed significant increases on the Authentic Happiness Inventory in the intervention condition at all follow-up points.…”
Section: Resultsmentioning
confidence: 99%
“…Some PPIs have been centred on single aspects, such as strengths, optimistic views of oneself, gratitude, or savouring positive events. These interventions showed increases in well‐being (Bolier et al, 2013; Proyer et al, 2016b), decreases in depressive symptoms (Bolier et al, 2013; Proyer et al, 2016b; Seligman, Steen, Park, & Peterson, 2005), and increases in PA (Emmons & McCullough, 2003; Sheldon & Lyubomirsky, 2006). Other PPIs have several components (Moskowitz et al, 2012; Proyer et al, 2016a; Roepke et al, 2015), and findings have highlighted decreases in depression (Roepke et al, 2015) and NA (Moskowitz et al, 2012) and increases in life satisfaction (Roepke et al, 2015) and PA (Moskowitz et al, 2012; Proyer et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence shows that an appreciation of beauty generally (rather than specifically natural beauty) is positively associated with prosociality and well-being ( Martínez-Martí et al, 2016 ). In an online empirical study, Proyer et al (2016) found increased levels of happiness at three time points after participants noted “beautiful things” in human behavior, nature and generally, the design did not allow the functional type of beauty to be identified. Given the benefits, there have been attempts to develop interventions to improve the appreciation of beauty, although Proyer et al (2016) noted a lack of intervention studies on appreciation of beauty, both human and nature focussed.…”
Section: Introductionmentioning
confidence: 99%
“…In an online empirical study, Proyer et al (2016) found increased levels of happiness at three time points after participants noted “beautiful things” in human behavior, nature and generally, the design did not allow the functional type of beauty to be identified. Given the benefits, there have been attempts to develop interventions to improve the appreciation of beauty, although Proyer et al (2016) noted a lack of intervention studies on appreciation of beauty, both human and nature focussed. Martínez-Martí et al (2014) , using a qualitative evaluation, found that a 3-week web-based intervention improved well-being and appreciation of beauty generally.…”
Section: Introductionmentioning
confidence: 99%